Проблеми примусового відчуження земельних ділянок сільськогосподарського призначення іноземцями та особами без громадянства - Наконечний, Андрій Богданович; Наконечный, Андрей Богданович; Nakonechnyi, Andriy B. (My University, 2015)
Стаття присвячена дослідженню норм чинного українського законодавства та сучасної судової практики щодо примусового відчуження земельних ділянок сільськогосподарського призначення іноземцями та особами без громадянства. Окреслено основні проблемні питання та запропоновано шляхи їх подолання.

Статья посвящена исследованию норм действующего украинского законодательства и современной судебной практики относительно принудительного отчуждения земельных участков сельскохозяйственного назначения иностранцами и лицами без гражданства. Определены основные проблемные вопросы и предложены пути их преодоления.

The article examines the current Ukrainian legislation and court practice on the question of compulsory acquisition of agricultural land by foreigners and stateless persons. Legal restrictions on obtaining the ownership of agricultural land by foreigners, foreign countries, stateless persons and other subjects are widely used in other countries. Ukraine also establishes the provision on the necessity of compulsory acquisition of agricultural land that have been inherited by foreigners or stateless persons. However, until now, any detailed legal procedure is not developed, creating inconvenience and confusion not only for such heirs, but even for government agencies. So, nowadays the registration process of inheritance rights on land by foreigners and stateless persons is not different from the procedure established for all citizens of Ukraine. But during the registration of inheritance, foreigners could not register agricultural land and obtain title documents for a long time. The problem of collision between the provisions of the existing land laws have been solved only on the basis of certain subordinate legal acts. More recently, courts have provided some explanations in the form of letters and other judicial precedents. They specify the ways of document registration, the beginning of the expiry of annual period of compulsory purchase and persons who can go to court. However, there are still a lot of legal issues on compulsory acquisition of agricultural land by foreigners. Firstly, it is the issue of the absence of legal procedure for enforcing foreigners to register such land and the absence of appropriate responsibility for using this land without title documents. Secondly, the lack of any records of inherited or registered agricultural land by foreigners and stateless persons as well as united agency of information gathering. Thirdly, there is no procedure or form of going to court by relevant authorities to enforce the sale of the above mentioned land. The author suggests the solutions to major problems by making appropriate legislative changes.
Наконечний А. Б. Проблеми примусового відчуження земельних ділянок сільськогосподарського призначення іноземцями та особами без громадянства / А. Б. Наконечний // Юридичний науковий електронний журнал: електронне наукове фахове видання [Електронний ресурс]. – 2015. – Режим доступу: http://lsej.org.ua/1_2015/25.pdf.
Keywords: примусове відчуження; іноземці; земельні ділянки; земельне законодавство; принудительное отчуждение; иностранцы; земельные участки; земельное законодательство; compulsory acquisition; foreigners; land; land legislation